Oral vinorelbine-based concomitant chemoradiotherapy in unresectable stage III non-small cell lung cancer: a systematic review. Issue 11 (2nd November 2018) - Lesueur, Paul; Martel-Laffay, Isabelle; Escande, Alexandre; Kissel, Manon; Locher, Chrystel; Gervais, Radj; Schott, Roland; Vergnenegre, Alain; Chouaid, Christos
ABSTRACT: Introduction : Cisplatin-based chemotherapy administered concomitantly to thoracic radiotherapy is the treatment recommended by the European guidelines for fit patients with unresectable stage III non-small cell lung cancer (NSCLC). Cisplatin may be combined with etoposide, vinorelbine or other vinca alkaloids, which act also as radiation sensitizers. Initially administered intravenously, vinorelbine is also available as oral formulation and is the only orally available microtubule-targeting agent. In addition, the oral formulation avoids the risk of extravasation and phlebitis. Areas covered : A literature search has been performed for articles reporting phase II–III trials aimed to evaluate efficacy and safety of oral vinorelbine-based chemoradiotherapy in unresectable locally advanced NSCLC. Expert commentary : In a series of trials with various protocols published from 2008 to 2018, mostly phase II studies, oral vinorelbine demonstrated a significant activity in concomitant chemoradiotherapy for unresectable locally advanced NSCLC typically as part of combination schedules with cisplatin. Main toxicities were hematologic (neutropenia and anemia); non-hematological toxicities included esophagitis and gastro-duodenal adverse events. Large prospective phase III trials are needed to confirm the role of vinorelbine-based chemotherapy associated to thoracic radiotherapy in unresectable stage III NSCLC and more particularly trials with metronomic oral vinorelbine.